“The Cloth that the Turkmān Took”: A Record of Trade in Plundered Goods from the Cairo Geniza? - Richard Dietrich (Al-Qantara : Revista de Estudios Arabes, 2024)
Although the Turks are infrequently mentioned the Cairo Geniza texts, two enigmatic lines in a 12th manuscript refer to a Jewish trader who leaves Damascus with cloth obtained by the Turkmen, but provide no explanation about why this trader would purchase textiles from them. Examination of other Geniza texts reveals a profitable trade in second-hand goods, clothes in particular. Some garments were obtained locally in Egypt, but other second-hand garments and textiles were purchased from unnamed suppliers outside of Egypt. Contemporary Arabic sources from Iraq also mention the trade in second-hand goods, but note that the purchase of Bedouin plunder supplied many of these items. This study suggests that the Jewish trader in Syria may have purchased textiles from the Türkmen who, like the Bedouin in Iraq, were selling their plunder. If this interpretation is correct, this Geniza manuscript along with others shed new light on the activities of the Turks in the Mediterranean basin in the decades following the Seljuq conquests in the Middle East and Anatolia.